Eksplorasi Minat Wakaf Uang Di Kalangan Pegawai Negeri Sipil: Studi Kasus Di Kantor Walikota Tangerang Selatan - Dyanti, Najwa Putri; Jaharuddin, Jaharuddin; Hartutik, Hartutik; Sukardi, Sukardi (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to determine the interest of Civil Servants (PNS) in cash waqf, with a case study at the South Tangerang Mayor's Office. Waqf is a crucial instrument in community economic empowerment, achieved by converting personal assets into communal ownership. This research employs a descriptive quantitative method with a sample of 150 respondents. Data analysis was conducted using the Partial Least Square method (SmartPLS 4.0). The results indicate that: (1) Religiosity does not have a significant effect on the interest in cash waqf; (2) Trust does not have a significant effect on the interest in cash waqf; (3) Service does not have a significant effect on the interest in cash waqf; (4) Promotion does not have a significant effect on the interest in cash waqf; and (5) Perception has a significant effect on the interest in cash waqf.